Manifestation of the structural stability of Mg-doped Zn4Sb3 via atomic fine structure investigation. (August 2017) - Wang, Y.; Feng, S.L.; Shen, K.C.; Sun, H.L.; Yang, Y.G.; Ji, G.W.; Li, J.; Jiang, Z.; Song, F.
Abstract: The structural stability is crucially important for thermoelectric material from the point view of energy harvesting applications. Herein, p-type Zn-Sb semiconductor doped with magnesium (Mg0.04 Zn3.96 Sb3 ) was experimentally investigated after thermal cycles to verify its structure stability, via a combination of synchrotron-based X-ray absorption spectroscopy (XAFS), grazing-incidence X-ray diffraction (GI-XRD), scanning electron microscopy (SEM), and energy dispersive spectrometer (EDS). While no visible structure change was discovered from XRD measurement after annealed to 573 K in air, well-preserved atomic structure of Mg-doped Zn-Sb was also demonstrated by XAFS. Interestingly, SEM indicated significantly improved surface morphology whilst EDS clearly showed the relative steadiness of each element's spatial distribution on surface. On basis of these findings, it was concluded in the end that the doping of magnesium substantially improves the thermal stability of zinc-antimonite compounds, and the possible mechanism underneath was also demonstrated. Highlights: The encouraging thermal stability of Mg-doped Zn4 Sb3 was manifested by XAFS and XRD. XAFS conveys the preservation of atomic fine structure of doped Zn4 Sb3 . A combination of XAFS, XRD and EDS reveals the possible mechanism of the enhanced stability of doped Zn4 Sb3 .